Greek font design: identifying preferable fonts for readers with dyslexia - Bilotti, Umberto; Demetriou, Kyriakos; Fella, Argyro; Todino, Michele Domenico (Frontiers in Computer Science, 2025)
The widespread adoption of modern artificial intelligence-based chatbots has revolutionised human–computer interactions. The use of these tools confirms reading as one of the primary ways of accessing information. The grapheme–phoneme conversion process is fundamental in learning to read and justifies the research for the development of tools capable of facilitating it. In the special case of a dyslexic student, the design choices related to a digital textual content cannot be a direct result of the aesthetic sense of the content creator. In this paper GreekDyslexic is presented, a Greek letter font that attempts to meet the characteristics proposed by the literature on high readability design. The production phases of GreekDyslexic are described, from the choice of elementary forms for their composition to the homogenisation process. This endeavour is driven by four key motivations: its application for native Greek speakers, its utility for learners of classical or modern Greek, the use of Greek letters in mathematics and physics, and its integration into digital museum materials. To achieve these objectives, a caption-based test is structured in which GreekDyslexic is compared to some of the most widely used fonts or those regarded as highly readable due to their sans serif nature. The test was administered to 98 Greek-speaking adults from Cyprus and Greece, 19 of whom reported a diagnosis of dyslexia. Despite being in the minority, a part of the sample rated GreekDyslexic positively. As a result, several potential solutions for future design interventions that effectively improve readability are suggested.